HOSPITAL-BASED PROSPECTIVE OBSERVATIONAL STUDY OF COMPLICATIONS IN CHILDREN WITH SNAKE BITE IN A TERTIARY CARE CENTER. - Jnanindra Nath Behera; Jatadhari Mahar; Nibedita Pradhan; Sucharita Meher; Birajman Lakra (Student's Journal of Health Research, 2023)
Objective: We attempted to study the complications of snake bites so that early recognition and institution of proper treatment can save the lives of many children. Methods: This Hospital based prospective observational study was conducted in Srirama Chandra Bhanj Medical College and Hospital, Cuttack from December 2020 to November 2022 among children aged 1-14 years with a history of snake bites admitted to our ward, through the outpatient department and emergency department. Results: Our study showed, that snake bite cases were predominantly seen in 8 -11 years of age with a male: female ratio of 2.9:1, as these age group children are actively engaged in outdoor games like playing near riverside and bushy areas in playgrounds. Acute markers as depicted by serum LDH, D-Dimer, Fibrinogen, and Ferritin were significantly high among haematotoxic cases due to secondary infection and correlated with cellulitis and necrotic ulcers which accounted for 57.1%. Conclusion: Healthcare providers should be made aware that a history of circumstantial evidence such as sleeping on the floor at night with sudden onset of pain abdomen, vomiting, and inability to keep the eyes open should prompt neurotoxic snake bite and ASV as well as Atropine, Neostigmine should be started. Recommendation: We recommend spreading more awareness, people should be counseled to use toilets more, to use mosquito nets while sleeping, avoid sleeping on the floor.